Study of da'wah texts on muslim.or.id: The perspective of Sara Mills' critical discourse analysis - Rifqi Syauqi Nur; Agus Riyadi (Islamic Communication Journal, 2023)
The massive transformation towards digitalization has brought about many innovative media approaches in preaching, such as the emergence of preaching websites and other platforms. The ease and fast process of publication have resulted in diverse texts of preaching, each with its unique characteristics. One of these websites is muslim.co.id, which focuses on discussing the virtues of men and glorification. This research is a qualitative study utilizing the critical discourse analysis model proposed by Sara Mills. The findings of this study reveal that the choice of words or phrases used and the focus of several articles on the Muslim.co.id website tend to exhibit a strong patriarchal tendency. This is evident through the gender issues in the texts and the superiority of men. Gender issues identified in the analysis include the subordination of women, stereotyping, and neglecting.  This study contributes to efforts to encourage the presence of egalitarian online religious media in accordance with religious (Islamic) principles that reject all forms of injustice. ***Transformasi besar besaran menuju digital memunculkan banyak inovasi media dakwah seperti hadirnya situs dakwah ataupun dalam platform yang lainnya. Kemudahan serta proses yang cepat untuk publikasi berdampak pada teks dakwah yang semakin beragam dengan keunikannya masing masing. Salah satu situs tersebut ialah muslim.co.id. Situs media dakwah tersebut mempunyai corak dakwah yang cukup konsen dalam membahas keutamaan laki laki dan glorifikasinya. Penelitian ini merupakan penelitian kualitatif dengan pendekatan critical discourse analysis model Sara Mills. Hasil dari penelitian ini mengungkapkan bahwa diksi atau kalimat yang dipakai serta konsen dari beberapa artikel yang ada di situs Muslim.or.id memuat tendensi patriarkal yang cukup lekat. Hal tersebut dibuktikan dengan objektifikasi perempuan dalam sebuah teks dan superioritas laki laki. Adapun isu gender yang dapat dideteksi ialah subordinasi perempuan, stereotiping, dan neglecting. Kajian ini berkontribusi bagi upaya mendorong hadirnya media keagamaan online yang egaliter sesuai dengan prinsip keagamaan (Islam) yang menolak segala bentuk ketidakadilan.